PEMBERIAN EKSTRAK MENIRAN (Phyllanthus niruri Linn) TERHADAP GAMBARAN HISTOPATOLOGI INFUNDIBULUM AYAM PETELUR YANG DIINFEKSI Escherichia coli - Irawan, Adinda Riezki; Sabdoningrum, Emy Koestanti; Hidanah, Sri; Chusniati, Sri; Madyawati, Sri Pantja; Tehupuring, Benjamin Christoffel (Universitas Airlangga, 2019)
The purpose of this research aimed to prove the effect of meniran extract (Phyllanthus niruri Linn) on layer hen infected with Escherichia coli to reduce inflammation and congestion on infundibulum histopathological view. This research used 20 samples of layer hen. The treatment in this research was P0- (not infected with Esherichia coli and did not treated with meniran(Phyllanthus niruri Linn)), P0+ (infected with Escherichia coli and did not treated with meniran(Phyllanthus niruri Linn)), P1 (infected with Escherichia coli and treated with 10% meniran extract (Phyllanthus niruri Linn)), P2 (infected with Escherichia coli and treated with 20% meniran extract (Phyllanthus niruri Linn)), P3 (infected with Escherichia coli and treated with 30% meniran extract (Phyllanthus niruri Linn)). The data of this study analyzed by Kruskal-wallis and followed with Mann-withney test. The result of this research can be concluded that 10% concentration of meniran extract (Phyllanthus niruri Linn) was effective to eliminate Escherichia coli, 20% concentration of meniran extract (Phyllanthus niruri Linn) able to promote antibacterial activity, and 30% concentration of meniran extract shown antibacterial rate on high potential so it can be used to reduce inflammation and congestion as the result of Escherichia coli infection.